Automation and computerization of processes of measuring thermoelectric parameters of materials forming part of generator and cooling thermoelectric modules - Anatychuk, L.I.; Havryliuk, M.V.; Lysko, V.V. (Journal of Thermoelectricity, 2021)
The results of development of automation system for measuring thermoelectric parameters of materials forming part of thermoelectric modules by the absolute method are presented. The measurement control unit is built on the basis of a multi-channel analog-to-digital converter. Processing and display of measurement results is carried out using a computer to which the measurement unit is connected via a standard USB channel. The results are displayed in the form of graphs and tables. The developed automation system is universal and makes it possible to measure the thermoelectric properties of materials both as part of generator and as part of cooling thermoelectric modules. Bibl. 9, Fig. 3.